Procedural aspects of the crime scene inspection as an investigative (search) activity: some issues for discussion - Y. Yu. Koniushenko (Law and Safety)
The article is devoted to some debatable issues of the crime scene inspection as an investigative (search) activity. The importance of researching the issues raised in the article is due to the fact that in practice, conducting various types of inspections is the most common procedural action aimed at collecting and verifying evidence. Attention is drawn to the lack of legislative interpretation of the concept of “crime scene inspection” (the provisions of Article 237 of the CPC of Ukraine define only the purpose of this procedural action), and doctrinal definitions of its legal understanding are given. The author's definition of the term “crime scene inspection” is a direct perception (research, study, observation) by the investigator, prosecutor with the participants involved in criminal proceedings (provided by the CPC of Ukraine) of the scene, area, premises, corpse, objects, documents and other material objects to identify and record information on the circumstances of the criminal offense. The existing views of individual lawyers in the scientific literature, according to which the examination is a kind of crime scene inspection are critically analyzed. It is determined that the examination is an independent investigative (search) action, which has specific goals and objectives, the range of participants and the procedure. Particular attention is paid to the inspection of the crime scene as an urgent investigative (search) action, it is determined that operatives do not have the right to conduct it. It is argued that the content of procedural activities during the crime scene inspection is not limited to the perception of criminal offenses traces and their reflection in the minds of investigators, prosecutors, it is also necessary that the received information is properly enshrined in the CPC of Ukraine procedural form. Based on the experience of the United States, including the Crime Scene Units and The Crime Scene Investigations Bureau, it was concluded that during the crime scene inspection to identify, capture and seize relevant objects,  which carry information about the circumstances of the criminal offense, a group of specialists from different fields of knowledge in accordance with their specialization but not one specialist should be involved according to Part 3 of Art. 237 of the PCP of Ukraine. Taking into account foreign experience, the opinion about the need to refuse the participation of witnesses during the investigative (search) actions has been expressed.